Assessing motivation and readiness to change for weight management and control: an in-depth evaluation of three sets of instruments - Ceccarini, Martina; Borrello, Maria; Pietrabissa, Giada; Manzoni, Gian Mauro; Castelnuovo, Gianluca (Frontiers in Psychology, 2015)
It is highly recommended to promptly assess motivation and readiness to change in individuals who wish to achieve significant lifestyle behavior changes in order to improve their health, overall quality of life and well-being. In particular, motivation should be assessed for those who face the difficult task to maintain weight, which implies a double challenge: weight loss initially and its management subsequently. In fact, weight-control may be as problematic as smoking or drugs-taking cessation, since they all share the commonality of being highly refractory to change behaviors. This paper will examine three well-established tools following the Trans-theoretical Model (TTM), specifically assessing readiness to change in weight management: the URICA, the S-Weight and the P-Weight and the Decisional Balance Inventory. Though their strengths and weaknesses may appear to be rather homogeneous and similar, the S-Weight and P-Weight are more efficient in assessing readiness to change in weight management and control. Assessing motivation and readiness to change may be a crucial step in promptly identifying psychological obstacles or resistance towards weight-management in overweight or obese hospitalised individuals, and it may contribute to provide a more effective weight-control treatment intervention.